2017
DOI: 10.1007/s10040-017-1550-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeological typologies of the Indo-Gangetic basin alluvial aquifer, South Asia

Abstract: The Indo-Gangetic aquifer is one of the world's most important transboundary water resources, and the most heavily exploited aquifer in the world. To better understand the aquifer system, typologies have been characterized for the aquifer, which integrate existing datasets across the IndoGangetic catchment basin at a transboundary scale for the first time, and provide an alternative conceptualization of this aquifer system. Traditionally considered and mapped as a single homogenous aquifer of comparable aquife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(70 citation statements)
references
References 72 publications
1
68
0
1
Order By: Relevance
“…Recent models for As‐affected aquifers in Southeast Asia have elucidated similar influential factors and variables (groundwater age, organic carbon, aquifer, depth, etc. ; Biswas et al, ; Biswas, Bhattacharya, et al, ; Biswas, Neidhardt, et al, ; Desbarats et al, ; Gillispie et al, ; McArthur et al, , , ; Mihajlov et al, ) related to modeled As hazard in aquifers (Biswas, Neidhardt, et al, ; Bonsor et al, ; Hoque et al, , , ; Mahmud et al, ; Mukherjee et al, ; Podgorski et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent models for As‐affected aquifers in Southeast Asia have elucidated similar influential factors and variables (groundwater age, organic carbon, aquifer, depth, etc. ; Biswas et al, ; Biswas, Bhattacharya, et al, ; Biswas, Neidhardt, et al, ; Desbarats et al, ; Gillispie et al, ; McArthur et al, , , ; Mihajlov et al, ) related to modeled As hazard in aquifers (Biswas, Neidhardt, et al, ; Bonsor et al, ; Hoque et al, , , ; Mahmud et al, ; Mukherjee et al, ; Podgorski et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Naturally occurring, geogenic arsenic (As) adversely affects drinking water quality of groundwater in geologically diverse aquifers in Europe, Africa, and North and South America, and particularly Southeast Asia (Amini et al, ; Bonsor et al, ; McArthur et al, ; Smedley & Kinniburgh, ; Wen et al, ). Within North America, naturally occurring As is widespread in groundwater throughout Late Quaternary glacial aquifers in the northern United States (Ayotte et al, ; Erickson, ; Root et al, ; Thomas, , ; Thomas et al, ; Warner, ; Warner & Ayotte, ; Welch et al, ; Ying et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no clear trend appears in South India [9,10]. These two contrasted results are mainly driven by the size of the groundwater resources: the presence in the north of the highest-yielding deep aquifers known in the world [11], contrasts with the southern aquifers, which consist of shallow to moderately shallow fractured hard rocks with low porosity and storage capacities [12]. Whereas in the north water extraction for irrigation purposes leads to a continuous decline in groundwater stocks, South Indian farmers experience recurring shortages, as shallow aquifers are temporarily emptied during periods of overexploitation when extraction is higher than recharge, and are partially refilled after heavy monsoon rainfalls.…”
Section: Introductionmentioning
confidence: 99%
“…They found that CHM structure uncertainty dominated over parameter uncertainty when the models were used for extrapolation. Many studies have recently suggested that uncertainty derived from the definition of alternative CHMs is one of the major sources of total uncertainty, and the parameter uncertainty does not cover the entire uncertainty range (Bredehoeft, 2005;Neuman, 2003;Refsgaard et al, 2006;Rojas et al, 2008;Troldborg et al, 2007). Therefore, neglecting the CHM uncertainty may result in un-reliable prediction and underestimate the total predictive uncertainty.…”
Section: Introductionmentioning
confidence: 99%